La formalización de los derechos de uso del agua y la propiedad hidráulica condicional en el valle del Colca, Perú - Stensrud, Astrid B. (2023)
This article discusses the production and negotiation of water ownership among peasant farmers in the Majes-Colca watershed in southern Peru, where the public water administration initiated a process of formalising user rights for potable water in 2011. While a large-scale irrigation project channels water from the headwaters to export-oriented agriculture in the desert, the supply of water is getting scarcer because of climate change. The Peruvian water resources law from 2009 acknowledges water as public property, yet emphasizes its economic value and encourages private investment. The farmers in the highlands see water not only as a resource but also as a life- giving force provided by the mountain-beings to the humans living in their domains. Seeing ownership as an on- going and dynamic process, and «commoning» as made by practices of nurture, the article argues that conditional forms of ownership emerge from relationships of reciprocity between humans and other-than-human beings. These are modes of ownership that exceed the dichotomies of private-public, commons-commodity and subject-object.